2012
DOI: 10.1099/jmm.0.047167-0
|View full text |Cite
|
Sign up to set email alerts
|

Desulfurization of mucin by Pseudomonas aeruginosa: influence of sulfate in the lungs of cystic fibrosis patients

Abstract: Pseudomonas aeruginosa is a common cause of chronic respiratory infection in cystic fibrosis (CF) patients. Infection is established within the lung epithelial mucus layer through adhesion to mucins. Terminal residues on mucin oligosaccharide chains are highly sulfated and sialylated, which increases their resistance to degradation by bacterial enzymes. However, a number of microbes, including P. aeruginosa, display mucin sulfatase activity. Using ion chromatography, the levels of sulfation on different respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 55 publications
2
28
0
Order By: Relevance
“…Previous studies have shown that mucins can support the carbon demands of P . aeruginosa in vitro [41,42]; however, these studies included autoclaved preparations of commercial porcine gastric mucin (PGM) that contain low molecular mass compounds that are readily utilized. In fact, when PGM preparations were filtered and dialyzed in our study (leaving only large, intact glycoproteins) appreciable growth of P .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that mucins can support the carbon demands of P . aeruginosa in vitro [41,42]; however, these studies included autoclaved preparations of commercial porcine gastric mucin (PGM) that contain low molecular mass compounds that are readily utilized. In fact, when PGM preparations were filtered and dialyzed in our study (leaving only large, intact glycoproteins) appreciable growth of P .…”
Section: Discussionmentioning
confidence: 99%
“…However, the process of mucin degradation, and its potential contribution to airway disease has not been addressed in detail. Previous studies have shown that mucins can support the carbon demands of P. aeruginosa in vitro [41,42]; however, these studies included autoclaved preparations of commercial porcine gastric mucin (PGM) that contain low molecular mass compounds that are readily utilized. In fact, when PGM preparations were filtered and dialyzed in our study (leaving only large, intact glycoproteins) appreciable growth of P. aeruginosa isolates was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…, homodimeric, NAD(P)H-consuming, flavin-cofactor-dependent, cytoplasmic oxidoreductases [14,23]). One such candidate was MsuE from P. aeruginosa , previously characterised as an NADH-dependent flavin mononucleotide (FMN) reductase that provides reduced FMN to power desulfonation of alkanesulfonates [24,25]. In an initial rapid qualitative test for nitroreductase activity, employing the nitro-quenched fluorophore FSL 61 as a generic nitroreductase substrate (as per [14]), a nitroreductase gene knockout strain of E. coli over-expressing MsuE from plasmid pUCX exhibited comparable levels of fluorescence to isogenic strains over-expressing E. coli NfsA (NfsA_Ec) or NfsB_Ec (Figure 1).…”
Section: Resultsmentioning
confidence: 99%